Tackling in rugby: Coaching strategies for effective technique and injury prevention - Hendricks, S.; Lambert, M. (International Journal of Sports Science and Coaching, 2010)
The high impact and physical nature of the tackle during a rugby match places the tackler(s) and ball-carrier at risk of injury. Injuries as a result of the tackle account for up to 61% of all injuries that occur during a rugby match. The purpose of this paper is to: i) review the literature on tackle injury mechanisms and events associated with increased risk of injury during the tackle; and ii) identify strategies that can be coached during training and executed by players during a match to reduce the risk of injury. Coaches equipped with a better understanding of injury mechanisms and a thorough knowledge of a safe and effective technique in the tackle have a major role in preventing or reducing tackle injuries.